Analisis Penyelesaian Sengketa dalam Perspektif Hukum Internasional (Studi Kasus Sengketa Satelit Komunikasi Pertahanan Indonesia dengan Navajo) - Tampubolon, Imagrace Triamorita; Shintauli, Margaretha; Permatasari, Audry (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research aims to analyze dispute resolution from the perspective of international law, using the case study of the defense communication satellite dispute between Indonesia and the Navajo company. The issues examined include the definition of international disputes and their resolution mechanisms under international law, as well as the chronology of the dispute between Indonesia and Navajo and the legal remedies available to Indonesia. The study adopts a normative juridical approach by examining international legal instruments such as the Charter of the United Nations, principles of international treaty law, and the practice of peaceful dispute settlement. The findings indicate that an international dispute is a disagreement between subjects of international law regarding their rights and obligations in international relations. The dispute arose when the Indonesian government unilaterally canceled a satellite orbit slot agreement managed by Navajo, prompting a claim for damages. Under international law, Indonesia may pursue peaceful means of dispute resolution, including negotiation, mediation, or international arbitration, in accordance with Article 33 of the UN Charter. This study emphasizes the importance of legal certainty in international agreements and the protection of state interests in cross-border legal relations.